1972
DOI: 10.1063/1.1654271
|View full text |Cite
|
Sign up to set email alerts
|

Influence of implantation temperature and surface protection on tellurium implantation in GaAs

Abstract: GaAs samples were implanted with tellurium at room temperature or at 150 °C and annealed to 750 °C with an SiO2 or Si3N4 protective layer. The highest electron concentrations and brightest photoluminescence were obtained for the hot implants with a Si3N4 protective layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…A long treatment at typical growth temperatures may remove one type of defect but has little effect on the other͑s͒. 21 As with PL efficiency and linewidth, it is important to compare the optimal annealing temperature between samples of identical structure. It is likely also beneficial to use PL test structures that reproduce the thermal cycling an active region experiences during device growth.…”
Section: Overannealing Effects In Gainnas"sb… Alloys and Their Importmentioning
confidence: 99%
“…A long treatment at typical growth temperatures may remove one type of defect but has little effect on the other͑s͒. 21 As with PL efficiency and linewidth, it is important to compare the optimal annealing temperature between samples of identical structure. It is likely also beneficial to use PL test structures that reproduce the thermal cycling an active region experiences during device growth.…”
Section: Overannealing Effects In Gainnas"sb… Alloys and Their Importmentioning
confidence: 99%
“…This is due p r i m a r i l y to the high anneal temperature used (900~ and not to the quality of the coatings, Harris et al (4) have reported a nne'aling GaAs at 750~ using Si3N4 coatings with little PL degradation, despite having problems with SigN4 adhering to the GaAs. This is due p r i m a r i l y to the high anneal temperature used (900~ and not to the quality of the coatings, Harris et al (4) have reported a nne'aling GaAs at 750~ using Si3N4 coatings with little PL degradation, despite having problems with SigN4 adhering to the GaAs.…”
Section: Fifl 2 Thermal Etch Pits Seen At 30 ~ Incidence In (100) Smentioning
confidence: 99%
“…SiO 2 film and SiN x film have also been used as the diffusion mask for selective masked diffusion of Zn. 5,7 However, from the standpoint of thermal mismatch and gallium-outdiffusion, [7][8][9][10][11][12][13][14] it is to be expected that aluminum nitride ͑AlN͒ would be preferable to SiO 2 , PSG or SiN x for both the anneal cap and the diffusion mask. In film etching, Zn x SiO y film deposited on an AlN film can be removed by means of preferential etching in buffered-hydrofluoric-acid, and the preferential-etching technique is useful for device processing.…”
Section: Introductionmentioning
confidence: 99%